Increased Cerebrospinal Fluid F(2)-Isoprostanes are Associated with Aging and Latent Alzheimer’s Disease as Identified by Biomarkers - Montine, Thomas J. (2010)
Alzheimer’s disease (AD) is a common age-related chronic illness with latent, prodrome, and fully symptomatic dementia stages. Increased free radical injury to regions of brain is one feature of prodrome and dementia stages of AD; however, it also is associated with advancing age. This raises the possibility that age-related free radical injury to brain might be caused in part or in full by latent AD. We quantified free radical injury in the central nervous system with cerebrospinal fluid (CSF) F(2)-isoprostanes (IsoPs) in 421 clinically normal individuals and observed a significant increase over the adult human lifespan (P < 0.001). Using CSF amyloid (A) β(42) and tau, we defined normality using results from 28 clinically normal individuals < 50 years old, and then stratified 74 clinically normal subjects ≥ 60 years into those with CSF that had normal CSF Aβ(42) and tau (n=37); abnormal CSF Aβ(42) and tau, the biomarker signature of AD (n=24); decreased Aβ(42) only (n=4); or increased tau only (n=9). Increased CSF F(2)-IsoPs were present in clinically normal subjects with the biomarker signature of AD (P < 0.05) and those subjects with increased CSF tau (P < 0.001). Finally, we analyzed the relationship between age and CSF F(2)-IsoPs for those clinically normal adults with normal CSF (n=37) and those with abnormal CSF Aβ(42) and/or tau (n=37); only those with normal CSF demonstrated a significant increase with age (P < 0.01). These results show that CSF F(2)-IsoPs increased across the human lifespan and that this age-related increase in free radical injury to brain persisted after culling those with laboratory evidence of latent AD.